Monophasic action potential recordings during acute changes in ventricular loading induced by the Valsalva manoeuvre. Issue 3 (March 1992) - Taggart, P; Sutton, P; John, R; Lab, M; Swanton, H
Abstract : OBJECTIVE--The strong association between ventricular arrhythmia and ventricular dysfunction is unexplained. This study was designed to investigate a mechanism by which a change in ventricular loading could alter the time course of repolarisation and hence refractoriness. A possible mechanism may be a direct effect of an altered pattern of contraction on ventricular repolarisation and hence refractoriness. This relation has been termed contraction-excitation feedback or mechano-electric feedback. METHODS--Monophasic action potentials were recorded from the left ventricular endocardium as a measure of the time course of local repolarisation. The Valsalva manoeuvre was used to change ventricular loading by increasing the intrathoracic pressure and impeding venous return, and hence reducing ventricular pressure and volume (ventricular unloading). PATIENTS--23 patients undergoing routine cardiac catheterisation procedures: seven with no angiographic evidence of abnormal wall motion or history of myocardial infarction (normal), five with a history of myocardial infarction but with normal wall motion, and 10 with angiographic evidence of abnormal wall motion--with or without previous infarction. One patient was a transplant recipient and was analysed separately. SETTING--Tertiary referral centre for cardiology. RESULTS--In patients with normal ventricles during the unloading phase of the Valsalva manoeuvre (mean (SD)) monophasic action potential duration shortened from 311 (47) ms to 295 (47) ms (p less than 0.001). After release of the forced expiration as venous return was restored the monophasic action potential duration lengthened from 285 (44) ms to 304 (44) ms (p less than 0.0001). In the group with evidence of abnormal wall motion the direction of change of action potential duration during the strain phase was normal in 7/21 observations, abnormal in 6/21, and showed no clear change in 8/21. During the release phase 11/20 observations were normal, five abnormal, and four showed no clear change. In those with myocardial infarction four out of five patients had changes that resembled those with normal ventricles but the changes were less pronounced. There were no differences in any of the three groups between the changes in monophasic action potential duration in patients taking beta blockers and those who were not. The changes in monophasic action potential duration in the transplanted heart resembled those in the group with normal ventricles. Inflections on the repolarisation phase of the monophasic action potential consistent with early afterdepolarisations were seen in three of the patients with abnormal wall motion and in none of those with normal wall motion. CONCLUSIONS--These results are further evidence that changes in ventricular loading influence repolarisation. When wall motion was abnormal the effects on regional endocardial repolarisation were often opposite in direction to those when it was normal. Thus regional differences in wall motion could generate local electrophysiological inhomogeneity which may be relevant to the association of arrhythmia with impaired left ventricular function.